2009
DOI: 10.1136/bmj.b784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food intake during labour on obstetric outcome: randomised controlled trial

Abstract: Objective To investigate the effect of feeding during labour on obstetric and neonatal outcomes. Design Prospective randomised controlled trial. Setting Birth centre in London teaching hospital. Participants 2426 nulliparous, non-diabetic women at term, with a singleton cephalic presenting fetus and in labour with a cervical dilatation of less than 6 cm. Intervention Consumption of a light diet or water during labour. Main outcome measures The primary outcome measure was spontaneous vaginal delivery rate. Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 26 publications
1
50
1
3
Order By: Relevance
“…Another study showed that food intake during labor did not increase the rate of maternal and fetal complications, or vomiting [13]. Duration of labor and number of operative deliveries were similar among women who were allowed to eat and those who only drank water during labor.…”
Section: Discussionmentioning
confidence: 97%
“…Another study showed that food intake during labor did not increase the rate of maternal and fetal complications, or vomiting [13]. Duration of labor and number of operative deliveries were similar among women who were allowed to eat and those who only drank water during labor.…”
Section: Discussionmentioning
confidence: 97%
“…The American College of Nurse-Midwives (2008) encourages the provision of nutrition to low-risk patients in labor to prevent ketosis and other problems associated with keeping a patient on a nothing by mouth (NPO) diet. Oral nutrition during labor does not influence either obstetric or neonatal outcomes (O'Sullivan, Liu, Hart, Seed, & Shennan, 2009). Another intervention as common as limiting oral intake from the woman is frequent vaginal examinations.…”
Section: Limited Oral Intake During Labormentioning
confidence: 99%
“…57,58 To date, five randomized controlled trials have evaluated labor outcomes following liquid or solid oral intake in lowrisk laboring women. [59][60][61][62][63] A Cochrane review of these studies (pooled n = 3130) found that there was no difference in the rate of cesarean delivery (average risk ratio 0.89, 95% CI: 0.63-1.25), operative deliveries (average risk ratio 0.98, 95% CI: 0.88-1.10), or Apgar scores < 7 at 5-min (average risk ratio 1.43, 95% CI: 0.77-2.68) between parturients allowed oral intake and those who had oral fluid restrictions. 64 The review did not identify evidence of harm from allowing oral intake, and therefore concluded that eating/drinking should be allowed during labor.…”
Section: Maternal Aspirationmentioning
confidence: 98%